2017
DOI: 10.3389/fphys.2017.00699
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Pattern, the Physiological Bases and the Molecular Mechanism of the Adductor Muscle Scar Pigmentation in Pacific Oyster Crassostrea gigas

Abstract: The melanin pigmentation of the adductor muscle scar and the outer surface of the shell are among attractive features and their pigmentation patterns and mechanism still remains unknown in the Pacific oyster Crassostrea gigas. To study these pigmentation patterns, the colors of the adductor muscle scar vs. the outer surface of the shell on the same side were compared. No relevance was found between the colors of the adductor muscle scars and the corresponding outer surface of the shells, suggesting that their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…As discussed earlier, CYP450 may affect orange coloration through the accumulation of different pigments in QN Orange scallops. In the Pacific oyster, CYP450 has been found to be differentially expressed in oysters with black tissues, suggesting that the CYP450 gene may be involved in melanogenesis [33]. Thus the possibility that CYP450 affects orange coloration through the accumulation of melanin in QN Orange scallops can not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, CYP450 may affect orange coloration through the accumulation of different pigments in QN Orange scallops. In the Pacific oyster, CYP450 has been found to be differentially expressed in oysters with black tissues, suggesting that the CYP450 gene may be involved in melanogenesis [33]. Thus the possibility that CYP450 affects orange coloration through the accumulation of melanin in QN Orange scallops can not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have shown strong positive genetic correlations (correlation coefficient range of 0.59-0.70) between growth related traits and body color in banana shrimp (Fenneropenaeus merguiensis) (Nguyen et al, 2014). In the Pacific oyster, the adductor muscle scar color was correlated with the soft-body dry weight, so the black adductor muscle scar may be a potential breeding character that could be used to obtain a larger soft-body dry weight (Yu et al, 2017). In some species of Drosophila, the melanin in the body is associated with heat resistance and has wound healing and immune functions (Rajpurohit et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
“…For example, the boring giant clam (Tridacna crocea) is polymorphic for mantle color, and the survival rate of the blue strain was significantly lower than the yellow-green strain (Zhou et al, 2021). In the black and white shell varieties of the Pacific oyster (Crassostrea gigas), the relationship between the color of the adductor muscle scars and the dried soft-body weight can be explained by the high hydroxyl free radical scavenging capacity of the muscle attached to the black adductor muscle scar (Yu et al, 2017). Genetic introgression caused by interspecific hybridization can lead to the segregation of pigment traits in progeny.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the formation and development of AM has a very important effect on the growth and diet of oysters. On the other hand, AM produces large amounts of melanin, and it is reported that the more melanin in the shell, the higher the dry weight of oysters (Yu et al 2017;Hao et al 2015;Xiao yan et al 2003). Melanin removes free radicals and reduces damage to AM, which allows AM to open larger shells and filter out more algae to speed up growth.…”
Section: Discussionmentioning
confidence: 99%